Revisiting English as a foreign language teachers’ professional identity and commitment in social media-focused professional development - Ping, Wenjiang (Frontiers in Psychology, 2022)
These days, technology advancement has inspired a large number of educators to employ social media in the English as a foreign language (EFL) context. But, some EFL educators are yet unwilling to use such chances, because they are left untrained. Therefore, applying professional development in this field appears necessary as it is regarded as the main cause of improving educators’ education activity, and proposing new education approaches. To strengthen the academic investment in educators’ professional learning, comprehending elements affecting educators’ performance of learning from professional development is vital. Lower commitment degrees were specified as an element that impedes EFL educators from employing social media in EFL education. Moreover, developing the professional identity of educators is an important issue that straightly pertains to educators’ performance, which assists educators both in comprehending their professional lives and presenting them with a framework to elucidate, expand and contemplate their professional activities. Stimulated by the interest in research on social media-focused courses, this review inspects how teachers’ commitment and identity affect EFL teachers’ implementation of social media in professional development. In a nutshell, implications for stakeholders of the study are presented. Indeed, the social media as an impotent device should be incorporated in PD programs to develop both teachers’ commitment and identity. Faculty members should establish workshops, and seminars to arrange for a platform for teachers to use social media to support learning.